Access to Safe Water Among Waterfront Dwellers in Port Harcourt Metropolis, South-South Nigeria - Opubo, Idoniboyeobu, Frances; O., Ekenedo, Golda (European Scientific Journal, ESJ, 2020)
The study examined access to safe water among waterfront dwellers in Port Harcourt Metropolis, Nigeria. The study further established effects of some demographic variables on access to safe water. A descriptive, crosssectional study was carried out among a population of 337,489 waterfront dwellers of the 40 waterfronts in Port Harcourt Metropolis using a sample of 1400 waterfront dwellers drawn through a multi-stage sampling procedure. Instrument used for data collection was 11-item structured questionnaire titled “Access to Safe Water Questionnaire” (ATSWQ) which has a reliability index of 0.97 and focus group discussion. Data collected was analysed using the Statistical package for Social Sciences (SPSS) version 10. Descriptive statistic of Mean was used to establish access to safe water while inferential statistic of Analysis of Variance (ANOVA) set at 0.05 level of significance was employed to determine the effects of demographic variables on access to safe water. The findings of the study revealed that waterfront dwellers in Port Harcourt Metropolis did not have access to safe water ( =1.01 < 2.0). Whereas significant difference existed in access to safe water among the waterfront dwellers based on educational status and family size (P=0.00 respectively), the contrary was the case in respect of marital status (P=0.89). The study concluded that the waterfront dwellers were at serious risk of waterborne diseases and required immediate intervention especially health education intervention.